EKPLORASI PENGOLAHAN SERAT SABUT KELAPA DENGAN PEWARNA ALAMI SECANG SEBAGAI MATERIAL ALTERNATIF FURNITUR - Ade Putri, Sindi; Fitra Andriana, Yunita; Septiana, Ulfa (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2019)
Indonesia is one of the countries in the world that produces highest amount of coconut.In a year, the amount of coconut fiber produced in Indonesia reached 18 million tons, but itsutilization has been done less than 5%. Even though the enormous amount of its production andits strong character havea high potential to be processed into more useful alternative materials,the utilization of coconut fiber is still limited in furniture and handicraft industries.Theexploration of coconut fiber as an alternative material was aimed to producing natural rawmaterials that are environmentally friendly and supporting the idea of using coconut fiber intoproducts that have high economic value. In addition, coloring process with sappan woodextraction has been conducted in this study in aim toelevatecoconut fiber aesthetic value.The method used in this study is descriptive experimental. In theapproaching process,several explorations were conducted to find the right technique in processing coconut fiber withthe natural dye of sappan. Furthermore, after the exploration process has been conducted, thecharacter of coconut fibers processed with resin has a strong character and good resistence byheat and water as well. It makes it suitable to be an alternative material for outdoor tables. Inaddition, the coloring exploration process of coconut fiber using sappan wood resulted colorrange from yellow to maroon.